2021
DOI: 10.4491/eer.2021.125
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of low impact development practices-bioretention systems towards urban flood resilience: case study of Novi Sad, Serbia

Abstract: Bioretention systems are globally the most accepted Low Impact Development (LID) practices. In this study, we simulated bioretention performances for four locations in the city of Novi Sad, with RECARGA modelling software. The primary objective of the research was to evaluate potential of bioretention systems for runoff reduction. The second research objective was to suggest RECARGA model as a support for future decision-making processes. Analysis of the sensitivity of bioretention design parameters on biorete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The average annual amount of precipitation in the city of Novi Sad and its settlements is 605 mm, namely 132.6 mm in winter, 138.9 mm in spring, 205.5 mm in summer and 128 mm in autumn, but there is an increase in maximum daily and average annual precipitation in the past few years (hidmet.gov.rs). Short-term rains of high intensity are becoming more frequent, in uencing that the total annual rain intensity has reached its maximum of over 1000 mm of rain per year and also contributing to the occurring of frequent ooding and pollution problems especially in the urban parts of the Novi Sad city (Greksa et al 2022).…”
Section: Assessment Of Rgs Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The average annual amount of precipitation in the city of Novi Sad and its settlements is 605 mm, namely 132.6 mm in winter, 138.9 mm in spring, 205.5 mm in summer and 128 mm in autumn, but there is an increase in maximum daily and average annual precipitation in the past few years (hidmet.gov.rs). Short-term rains of high intensity are becoming more frequent, in uencing that the total annual rain intensity has reached its maximum of over 1000 mm of rain per year and also contributing to the occurring of frequent ooding and pollution problems especially in the urban parts of the Novi Sad city (Greksa et al 2022).…”
Section: Assessment Of Rgs Performancesmentioning
confidence: 99%
“…that can be described as a small-scale NbS that are specially designed to collect, absorb and lter stormwater runoff from impervious areas, both in private gardens as well as in the urban context ( In Serbia, the NbS concept is still in the initial process of implementation. RGs as part of the NbS have been identi ed and proposed as a promising NbS approach to enhance stormwater management and generally sustainable development in Serbia, in particular in the direction of overcoming the challenges in mitigation of existing problems with urban oods and pollution (Đurakovac et al 2018;Greksa et al 2022; Ljubojević et al 2022), but limited research is available on RGs performances in practice. Unlike previous studies, this paper aims to give concrete examples of installed RGs.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy includes using technologies such as permeable pavement, green roofs, rainwater harvesting, and others. Low Impact Development (LID) has been recommended for stormwater management and urban planning, which approaches sustainability and aims to reduce the negative impacts of rising urbanization and impervious surfaces [10], [11]. LID refers to practices and principles concerning specific sustainable water conservation goals [12], such as reducing run-off, recharging groundwater, protecting streams, increasing infiltration, and assessing water quality [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have shown that bioretention systems are also an effective solution for reducing rainwater runoff from catchment areas. Greksa et al [36] conducted BRS simulation studies for four sites and obtained the total average volume reduction, ranging from about 43% to 94%. On the other hand, researchers from Brazil obtained a 70% runoff reduction capacity for the case in which treated rainwater in a bioretention cell was directed to a reservoir, from which the water was a source for non-potable uses [37].…”
Section: Introductionmentioning
confidence: 99%